2018
DOI: 10.1371/journal.pone.0192285
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of Paradiplozoon homoion: A diplozoid monogenean exhibiting highly-developed equipment for ectoparasitism

Abstract: Diplozoidae (Monogenea) are blood-feeding freshwater fish gill ectoparasites with extraordinary body architecture and a unique sexual behaviour in which two larval worms fuse and transform into one functioning individual. In this study, we describe the body organisation of Paradiplozoon homoion adult stage using a combined approach of confocal laser scanning and electron microscopy, with emphasis on the forebody and hindbody. Special attention is given to structures involved in functional adaptation to ectopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 45 publications
7
31
0
Order By: Relevance
“…In our study, muscle fibres intensively stained with phalloidin were observed around the mouth opening of C. leptogaster as well as in the attachment organ and around the reproductive pore and vaginae. The data obtained correspond to those for other monogenean species G. rysavyi, M. congolensis and Paradiplozoon homoion (Bychowsky et Nagibina, 1959), in which muscle fibres were detected in the attachment organs, as well as in the ducts of the digestive and reproductive systems (Arafa et al 2007, Hodová et al 2018.…”
Section: -нт-Immunopositive Nerve Elements In Attachment Organssupporting
confidence: 84%
See 2 more Smart Citations
“…In our study, muscle fibres intensively stained with phalloidin were observed around the mouth opening of C. leptogaster as well as in the attachment organ and around the reproductive pore and vaginae. The data obtained correspond to those for other monogenean species G. rysavyi, M. congolensis and Paradiplozoon homoion (Bychowsky et Nagibina, 1959), in which muscle fibres were detected in the attachment organs, as well as in the ducts of the digestive and reproductive systems (Arafa et al 2007, Hodová et al 2018.…”
Section: -нт-Immunopositive Nerve Elements In Attachment Organssupporting
confidence: 84%
“…According to Cable et al (1996), two pairs of serotoninergic neurons have been found in the haptor of the monogenean Discocotyle sagittata (Leuckart, 1842). The innervation of the attachment organs by serotoninergic nerve fibres was also observed in E. nipponicum, P. integerrimum, P. homoion and M. congolensis (McKay et al 1991, Zurawski et al 2001, Hodová et al 2018.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The tegument is the epidermis of monogeneans; it has several functions, such as absorption and secretion of substances, osmoregulation, mechanical support, and protection against xenobiotics [ 99 ]. The parasite’s tegument is the first contact site for AgNPs, which cause damage at the ultrastructural level [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prominent annular ridges and extensions of the E. nipponicum hindbody are considered to be important for attachment and securing the position of the parasite among the secondary gill lamellae, somewhat analogous to a zip fastener [11]. Less prominent tegumentary folds and three highly mobile lobes have been described on the haptor of P. homoion [15].…”
Section: Self-protection Against the Environment And Excretory/secretmentioning
confidence: 99%